The polysemy of the prefix “des-” in action substantives based on “-ção” and “-mento” - Pereira, Carlos Gustavo Camillo (2021)
This paper investigates the meanings of the prefix "des" in action nouns in Brazilian Portuguese through an approach to the language in use and focuses on the importance of context for the recognition of the meaning being activated by the affix. Initially, the main contributions of the Normative Grammatical Tradition and the Theory of Generative Linguistics to the analysis of the referred prefix are presented. The corpus used in this research was constituted from the electronic mega-corpus NILC of the University of São Paulo developed on the São Carlos campus. The results of the data analysis reveal that the meaning of the affix “des-” in the language in use is highly influenced by the context, therefore it is possible for the same word to have different meanings, depending on whether it is in different situations of use.